2016
DOI: 10.1017/s0144686x16000106
|View full text |Cite
|
Sign up to set email alerts
|

Developing the assistive technology consumer market for people aged 50–70

Abstract: Within the United Kingdom (UK), assisted living technologies are mostly provided through statutory health and social care services following assessment of individual need and application of eligibility criteria. This paper describes the first UK study to explore and develop business approaches and innovations required to make electronic assisted living technologies more accessible to consumers in their fifties and sixties. A robust mixed-method approach was used including a large sample size for a consumer sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…As in other research,19 44 45 ease of use, providing a sense of reassurance, considerations of safety and autonomy were all reasons for carers to consider using AT. Similar to other reports on caring for an elderly population in the community,23 46 we found that carers continued to use AT regardless of having an increase in formal care services or having to find information and fund the purchase of the AT themselves. AT appeared to complement carer support by redeployment of carer time to more meaningful activities and interactions with the person with dementia.…”
Section: Discussionsupporting
confidence: 88%
“…As in other research,19 44 45 ease of use, providing a sense of reassurance, considerations of safety and autonomy were all reasons for carers to consider using AT. Similar to other reports on caring for an elderly population in the community,23 46 we found that carers continued to use AT regardless of having an increase in formal care services or having to find information and fund the purchase of the AT themselves. AT appeared to complement carer support by redeployment of carer time to more meaningful activities and interactions with the person with dementia.…”
Section: Discussionsupporting
confidence: 88%
“…The main factors limiting NMR adherence could all be addressed through the use of real time digital technology. However, for the type of wearable technology being considered, product design will be an additional factor likely to influence adherence [ 64 ], especially in the younger 30- to 45-year age group affected by this condition [ 3 ]. However, although the study clearly demonstrates positive attitudes toward the introduction of digital technology, economic barriers may prove to be a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Various products currently exist to support older people in their own homes, although there is evidence of limited mass-market adoption by older adults living at home [10] and a poor fi t between people's daily lives and the technologies produced [11,12]. One reason may be insuffi cient involvement of older people in the design of these technologies [13].…”
Section: Current Technology Landscapementioning
confidence: 99%